Analysis of The Relationship Between Gross Domestic Product and Indonesian Exports (Granger causality test) - Debora Silvia Hutagalung; Junaidi Siahaan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2020)
This study entitled "Analysis of The Relationship Between Gross Domestic Product and Indonesian Exports (Granger causality test)”. This research was conducted because of the dualism of the theory between the two variables. In macroeconomic theory, the relationship between Gross Domestic Product is one of the similarities, because exports contribute to Gross Domestic Products on the demand side, while neoclassical trade theory emphasizes causality related to household production and assistance for exports. The purpose of this study is to determine the relationship between Gross Domestic Product and exports. This study uses several analytical methods: Unit Root Test, Cointegration Test, Granger Causality Test using the E-views program7 and using Quarterly data. The results of the estimation of this study are the estimation of the relationship in GDP and exports, or in other words, the Gross Domestic Product affects Indonesia's exports. This is concluded based on the estimation results that can be seen from the statistical F value that is greater than the f-table (8.958205> 3.841466) on the Null hypothesis. GDP is not an Export Granger with a 95% confidence level. This means GDP affects exports When GDP can affect the level of exports in the intervals of 2000 to 2012.